Pengaruh Media Sosial, E-wom, Citra Merek, Kualitas Pelayanan terhadap Kepuasan Pelanggan di R Hotel Rancamaya - Azzahra, Annisa; MH Nainggolan, Bonifasius (CV. Lafadz Jaya, 2022)
This study aims to partially and simultaneously analyze the various independent variables used for research such as Social Media, E-WOM, Brand Image, and Service Quality to Customers at R Hotel Rancamaya. This research study uses quantitative methods and uses a purposive sampling technique for respondents. Researchers distributed questionnaires to 100 respondents by holding random sampling. This research uses Multiple Linear Regression technique. With the results obtained indicate that if Social Media has a significant and positive effect on customer satisfaction, E-WOM also has a significant and positive effect on customer satisfaction, Brand Image has a significant and positive effect on customer satisfaction and Service Quality is quite significant and worthy of the satisfaction obtained by the customer. It can be said that the media needs to be improved and interact more actively with consumers, most people see the ratings and reviews owned by R Hotel Rancamaya